Analysis of jogai during judo matches for athletes with visual impairments: impact on referee decisions and outcomes - Kons, R. L.; de Almeida, K. F.; Carpinelli, Y. F.; Detanico, D. (Adapted Physical Activity Quarterly, 2025)
This study investigated how jogai frequency influences referee decisions and match outcomes in judo athletes with visual impairment during official competitions. Video analysis of 268 matches revealed 1,395 instances of jogai, with 211 matches experiencing jogai and 57 without. Associations were carried out between jogai occurrences and match duration, sport classes, sexes, weight categories, and referee decisions post-jogai using chi-square tests (p < .05). Significant associations were found between jogai and match duration (x2 = 39.08, p < .001) and competition phase (x2 = 29.43, p = .043), particularly with frequent match stoppages (mate) within the first minute across all phases. These findings suggest a need for further research and potential adjustments in judo rules, informed by the new evidence-based classification, to enhance the equity and safety of matches for athletes with visual impairments.